HARNESSING MICROBIAL CONSORTIA FOR NEXT-GENERATION BIOFERTILIZERS AND BIOCONTROL AGENTS: MECHANISMS, CHALLENGES, AND OPPORTUNITIES. A REVIEW - Ayuba, K. S.; Ogbonnaya, C. S.; Tanko, F.; Yahaya, M. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
Nigerian agriculture faces persistent soil fertility depletion, rising costs of synthetic fertilizers, and environmental degradation, necessitating the need for sustainable, environmentally friendly and cost-effective alternatives to chemical inputs. This review evaluates the application of microbial consortia as biofertilizers and biocontrol agents in Nigeria, focusing on their benefits, constraints, and prospects for adoption. Relevant empirical studies on plant growth-promoting microorganisms, multi-strain inoculants, and biological pest suppression were reviewed to assess agronomic performance, implementation challenges, emerging innovations and adoption constraints. Microbial consortia enhance biological nitrogen fixation, phosphorus solubilization, nutrient cycling, plant defence responses, and phytohormone production leading to improved crop growth, soil health, and resilience to abiotic stress. Beneficial taxa such as Trichoderma, arbuscular mycorrhizal fungi and Pseudomonas suppress soil-borne pathogens, reducing pesticide dependence. However, inconsistent field performance, formulation challenges, short shelf life, weak quality control, limited farmer awareness, and inadequate production and regulatory systems constrain large-scale adoption. With improved formulation technologies, development of indigenous microbial strains, stronger extension services, and supportive policies, microbial consortia offer a viable pathway toward sustainable intensification, reduced agrochemical reliance, and enhanced productivity in Nigerian agriculture.